Do depressive symptoms among pregnant women assisted in Primary Health Care services increase the risk of prematurity and low birth weight? - Anelise de Toledo Bonatti; Ana Paula dos Santos Costa Roberto; Thais de Oliveira; Milena Temer Jamas; Maria Antonieta de Barros Leite Carvalhaes; Cristina Maria Garcia de Lima Parada (Universidade de São Paulo, 2021)
Objective: to investigate associations between depressive symptoms during pregnancy, low birth weight, and prematurity among women with low-risk pregnancies assisted in public Primary Health Care services. Method: prospective cohort with 193 pregnant women, using the Edinburgh Postnatal Depression Scale, telephone interviews, and medical records available in the health services. Associations of interest were obtained using the Cox regression model. Results: the participants were aged 24.9 years old (median) and had 11 years of schooling (median); 82.4% lived with their partners, and gestational age at the birth was 39 weeks (median). Twenty-five percent of the participants scored ≥13 on the Edinburgh scale. Depressive symptoms did not appear associated with low birth weight (RR=2.06; CI95%=0.56-7.61) or prematurity (RR=0.86; CI95%=0.24-3.09) in the adjusted analysis. However, premature labor increased the risk of low birth weight (RR=4.81; CI95%=1.01-23.0) and prematurity (RR=7.70; CI95%=2.50-23.7). Additionally, each week added to gestational age decreased the risk of low birth weight (RR=0.76; CI95%=0.61-0.95). Conclusion: the presence of depressive symptoms among women with low-risk pregnancies was not associated with low birth weight or prematurity.